Estudo de processos inflamatórios em modelo experimental de adicção induzida por cocaína e nicotina - Magda Luciana de Paula Rosa (2021)
Substance use disorder (addiction) is a chronic illness characterized by an inability to regulate drug-seeking behavior. The release of dopamine in the nucleus accumbens is known to be essential for the enhancing effects of cocaine. Nicotine also stimulates the mesolimbic dopaminergic system (reward system) which plays an important role in drug seeking. Studies have shown that the use of these drugs can interfere with the production and release of cytokines, suggesting a relationship between inflammation and addiction. Understanding this relationship can be important in the search for new therapeutic targets and treatment development. Thus, the present study aimed to investigate the role of inflammatory mediators and neurotrophic factors in a behavioral model of conditioned place preference (CPP), induced by the administration of cocaine and nicotine, in mice. Initially, two apparatuses that differed by the number of compartments were tested. Cocaine-induced conditioning was demonstrated in both. However, brain levels (prefrontal cortex, hippocampus and striatum) of cytokines and neurotrophic factors (IL-1β, IL-6, IL-10, TNF-α, CX3CL1, BDNF, GDNF and NGF) were different depending on the number of compartments in each apparatus. In general, the levels were found to be increased in the saline groups conditioned in the three-compartment apparatus, when compared to the same group conditioned in the two-compartment apparatus, suggesting that the choice of apparatus to be used in CPP studies may influence the research results. When comparing the saline and cocaine groups, conditioned in the three-compartment apparatus, the cocaine group showed a reduction in the levels of IL-1β, IL-6, IL-10, GDNF in the prefrontal cortex and CX3CL1 in the striatum. The experiments to analyze the levels of inflammatory mediators and neurotrophic factors in mice subjected to nicotine-induced CPP were performed in a three-compartment apparatus. Increased peripheral levels of IL-6 and IL-10, increased NGF levels and decreased GDNF in the hippocampus were observed in mice treated with nicotine. In the striatum there was a decrease in the levels of IL-1β, IL-10 and GDNF. Subsequently, treatment with clavulanic acid (CA) in cocaine-conditioned animals was analyzed. The doses of CA used did not prevent cocaine conditioning, when administered thirty minutes before the drug injections or when administered in a three-day pre-treatment. Possibly, the mechanisms involved in the increase of GLT-1 expression by CA should require more days of pretreatment. These results provide evidence for the role of cytokines and neurotrophic factors in cocaine- and nicotine-induced CPP. Therapeutic strategies can be developed with an understanding of inflammatory and neurotrophic mechanisms related to addiction in a behavioral model of location-conditioned preference.